Financialization and the Three Utopias of Shadow Banking. (1st August 2013) - Kessler, Oliver; Wilhelm, Benjamin
<x xml:space="preserve">Abstract</x> The shadow banking system has been identified as a central cause of the current economic crisis. In this article we clarify how the concept of shadow banking is used in public reports to inform current debates about its regulation. We argue that the debate on the regulation of shadow banking is based upon three utopias: the search for a homogenization of different regulatory spaces; the focus on a temporality based on always present availability of data; and the assumption of static configurations of actors within the financial system. Finally, we propose an alternative reading of shadow banking based on the concept of financialization. Financialization allows us to link shadow banking to questions of authority and legitimacy in financial markets. The politics of financialization in general and shadow banking in particular are linked to the stabilization of interpretations and fixation of meaning.